Detecting mitochondrial signatures of selection in wild Tibetan pigs and domesticated pigs. (2nd January 2016) - Li, Mingzhou; Jin, Long; Ma, Jideng; Tian, Shilin; Li, Ruiqiang; Li, Xuewei
Abstract: Selection in genomic regions is prevalent in mammals; however, the effects of selection on the mitogenome are not clearly understood. We determined the complete mitochondrial DNA (mtDNA) sequences from six wild Tibetan pigs from the Tibetan plateau and four domestic pig breeds from the lowland of neighboring southwest China. Nucleotide diversity analysis using the sliding window method showed that the nucleotide diversity of wild Tibetan pigs in most regions of the mitogenome was higher than that of domestic pigs. The 12 s ribosomal RNA showed relatively lower nucleotide diversity in Tibetan pigs, suggesting purifying selection of these genes during high-altitude adaptation. More non-synonymous nucleotide substitutions in the ATP6 were found in wild Tibetan pigs, indicating adaptive selection in Tibetan pigs. The results suggested distinct impacts of natural selection and artificial selection upon the mitogenome, especially the mitochondrial signatures of adaptive evolution in wild Tibetan pigs under natural selection.